(untitled) (Journal of Dhaka Medical College, 2018)
Aims: The present study was performed to investigate the hypolipidaemic effect of natural honey in hyperlipidaemic rats. We also compared the hypolipidaemic effects of natural honey with a standard known hypolipidacmic agent, atorvastatin. Methods: At first the rats (n=42), were randomly divided into six groups. Each group composed of seven rats. Group A control group received normal diet, distilled water for 10 days. Group B hyperlipidemic group received normal diet olive oil (1.5inl) with cholesterol daily for 10 days. Group C received normal diet, distilled water. D, E & F. On the 11th day of experiment the final body weight was measured & blood was collected by cardiac puncture for the study of lipid profile. Result: Only cholesterol fed Group B and C rats gained body weights. Natural honey and atorvastatin treated group of rats. Group D, E, F lost body weights. These changes between the initial and final body weight were statistically significant (p<0.05). Regarding the lipid levels, it was observed that (a) there as statistically significant rise of serum TCI., LDL & TG levels in group B compared to that of group A (p <0.001 in each parameter), b the serum TCL is significantly decreased in group B (p<0.05), and group F (p<0.01) in the comparison to groups; the value also decreased in group D but the decrease was slightly significant (C) the serum LDL level significantly reduced in group D, E & F compared to group C; but the maximum effect comparison to group C; the value also decreased in group D but the decreased was slightly significant. (C) the serum LDL level significantly reduced in group D, E & F compared to group C, but maximum effect was observed in group E & F (p <0.001). (d) No significant change of serum HDL was observed in Group D but slightly significantly increased in group E and group F (p <0.05) compared to group C. (e) The serum TG level reduced significantly (p <0.001) in group D. E and F compared to group C. Thus study showed natural honey reduced TCL, LDL & TG and slightly increase HDL and atorvastatin reduce TCL, LDL & TG. But atorvastatin have some side effect on the other hand natural honey have no side effect. Conclusion: The result and observation of the present study provide a rationale for use of natural honey in the development of a new herbal medicine much needed for the reduction of serum lipid levels (TCL, TO, LDL). Atorvastatin also lower TCL, LDL & TO. Thus it could he useful in hyperlipidaemic conditions. But before establishing natural honey as a therapeutically effective hypolipideamic agent, further studies should be carried out to determine the active principles responsible for hypolipidaemic effect and its cellular mechanism of action. J Dhaka Medical College, Vol. 26, No.2, October, 2017, Page 94-102